Informatização da rede de bibliotecas da Secretaria Municipal de Educacao de Florianópolis Library network informatization process on the Florianópolis Education Department p. 211-222 - Silva, Fernanda Claudia Lückmann da; Alves, Gisele; Viapiana, Noeli (Revista ACB, 2008)
Resumo:Relata o processo de informatização da Rede de Bibliotecas da Secretaria Municipal de Educação de Florianópolis. Breve histórico com o WinISIS até a implantação do Pergamum - Sistema Integrado de Bibliotecas. A implantação do Pergamum. Essa rede é composta de 38 bibliotecas escolares, 1 Biblioteca localizada no Centro de Educação Continuada da própria Secretaria e 37, nas Escolas do Ensino Fundamental, designadas Bibliotecas Escolares e Comunitárias. Abstract:This work present the library network informatization process by the Florianópolis Education Department. Give a introduction about the WinISIS until the migration process to the Pergamum integrated library system. Describes some system applications about the Pergamum. The library system network composition by 38 school libraries, 1 library is located in Continuous Education Center of the Education Department of Florianópolis and 37 are by the Elementary schools, called school and community libraries to benefit students and the district communities.